Modelling “the Expanding Circle” of Cooperation Towards a Sustainable Future - R. Smith, Steven (European Journal of Sustainable Development, 2017)
Can human cooperation expand to the global scale in time to avert catastrophic climate change? Prospects for a sustainable future depend on binding commitments that respect biophysical limits, which in turn depend on political support and global/intergenerational levels of moral concern. Numerous studies in the social sciences indicate that transcending parochial, group-level cooperation to the global scale requires some form of unifying "superordinate goal". This research explores what this transformative humanitarian goal might consist of, and what factors most influence the dynamics of human cooperation. Two quantitative models of cooperative social dynamics are developed and analysed: 1) Historical - analysing the global growth of social insurance provision and the abolition of slavery, including their key structural (macro) predictors; 2) Experimental - analysing the dynamics of cooperation and the consideration of future generations in a multiplayer social dilemma game. Longitudinal growth curve modelling (LGCM) of these models’ data allows many variables to be simultaneously combined into a single group of path coefficients, represented as a network of relationships over time. Preliminary results in the historical model a) confirms the view that social complexity expands more rapidly than cooperation, b) The rate of acceleration of cooperation required to ensure sustainability within the available time greatly exceeds the historical trend. Keywords: cooperation, dynamics, sustainability indicators, co-conn ratio, social movements, cultural evolution, future generations